IMPLEMENTASI PEMBELAJARAN HANDS ON ACTIVITIES UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN FISIKA SMP - Agustia, Zalpita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research aimed to describe the improvement of studentsâ critical thinking skill through the implementation of Hands on Activities on subject pressure. The study was conducted on 39 eighth grade students of 20 Junior High School in Pekanbaru. The design of this research was a pre-experimental with one group pretest-posttest design. The data of critical thinking skill was taken from the test. Descriptive analysis was used to see the improvement of studentsâ critical thinking skill from N-Gain score. The results indicated that there was a medium improvement of studentsâ critical thinking skill. Therefore, it can be concluded that the implementation of Hands on Activities on subject pressure able to improve critical thinking skill of eighth grade students at 20 Junior High School in Pekanbaru.Key Words: Hands on Activities, Critical Thinking Skill.